PENGARUH SEMANGAT KERJA, INSENTIF DAN SISTEM BIROKRASI TERHADAP KINERJA PEGAWAI DINAS PEMBERDAYAAN MASYARAKAT DAN DESA KABUPATEN PONOROGO - hestiningtyas, grina (Universitas Slamet Riyadi, 2020)
This study aims to determine and analyze the significance of work motivation, incentives, and bureaucratic systems simultaneously on the Employee Performance of the Community Empowerment Office and the Village of Ponorogo Regency. The population of this research is all employees of the Community Empowerment Office and the Village of Ponorogo Regency, the research sample is 30 people. The technique of collecting data uses validity and reliability tests. Analysis techniques through multiple regression analysis, t test, F test and R2. The analysis results obtained: The work spirit is not significant to the performance of the Ponorogo Village Empowerment and Community Service employees. Positive and significant incentives for performance for Ponorogo Village Empowerment and Community Service employees. The bureaucratic system has a positive and significant effect on the performance of the Ponorogo Regency Empowerment and Community Service staff. The conclusion of this study is that there are some significant incentives and bureaucratic systems to the performance of the Ponorogo Village Empowerment and Community Service employees.Â Keywords: work morale, incentives, bureaucracy system, employee performance.Â